Manifestasi Carbon Emission Disclosure Ditinjau Melalui Karakteristik Perusahaan dan Trading Carbon - Wahyuningsih, Rita; Hanifah, Umi; Meikhati, Ety (AKTSAR: Jurnal Akuntansi Syariah, 2023)
Climate change has evolved into a pressing global concern, prompting a concerted effort towards achieving net zero emissions as outlined in the Kyoto Protocol and Paris Agreement. In line with this urgency, this research focused on carbon emissions disclosure. This study aims to explore the determinants of carbon emissions disclosure among energy sector companies listed on the IDX between 2018 and 2022. Using a purposive sampling technique, we selected a sample of 17 companies based on predetermined criteria. Employing a quantitative approach, specifically panel data regression analysis, we investigated the influence of various factors including company size, profitability, company growth, media exposure, board gender diversity, and carbon trading on carbon emissions disclosure. The results show that the company growth and board diversity gender variables influence carbon emission disclosure, while the carbon trading variables and company characteristics which are proxied by company size, profitability, and media exposure do not affect carbon emission disclosure.